Pengembangan Komik Elektronik Kimia pada Materi Pokok Ikatan Kimia untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik Kelas X - Marwah, Siti; Ramlawati, Ramlawati; Syahrir, Muhammad (Chemistry Education Review (CER), 2021)
This study aims to designing chemistry learning media, namely chemistry electronic comic to improve the motivation and student learning outcomes on subject metter of chemical bonding and examining the quality of chemistry electronic comic obtained is valid, practical and effective. The development employed referred to Plomp's model which consisted of 3 main phases, namely (1) preliminary research, (2) development or prototyping phase, and (3) assessment phase. The target of this research are students of class X MIA 5 SMAN 14 Makassar with a total of 30 students. The result of the research shows that : (1) the validity of chemistry electronics comic was based on the media experts obtained the mean score 3.87 which was in very valid category, and the material expert namely 3.62 (very valid) category; (2) the practicality was based on: (a) the learning implementation employed chemistry electronics comic obtained 1.76 which was in “fully implemented” category, (b) the teacher's response on chemistry electronics comic obtained 3.77 (practical) , (c) the students' response on chemistry electronics comic obtained 87.6 (strongly responded); (3) the effectiveness was based on: (a) the students' activities obtained 87.16% which had met “excellent” criteria, (b) the students' learning motivation obtained 81.22% (very high), (c) the learning outcomes test obtained the mean score of pretest was 13.67% (low) and the posttest was 80% (high), and the result of N-gain 0.71 (high).